Root exudates regulate soil antibiotic resistance genes via rhizosphere microbes under long-term fertilization - Xiujing Guan; Yuhui Li; Yanying Yang; Zihua Liu; Rongguang Shi; Yan Xu (Environment International)
Organic fertilizer application promotes the prevalence of antibiotic resistance genes (ARGs), yet the factors driving temporal differences in ARG abundance under long-term organic fertilizer application remain unclear. This study investigated the temporal dynamics of ARG diversity and abundance in both bulk and rhizosphere soils over 17 years (2003–2019), and explored microbial evolution strategies, ARG hosts succession and the influence of root exudates on ARGs regulation. The results showed that the ARGs abundance in rhizosphere soil was lower than that in bulk soil under long-term fertilization, and ARGs abundance exhibited a decrease and then remained stable in rhizosphere soil over time. There was a strong association between host bacteria and dominant ARGs (p < 0.05). Structural equations demonstrated that bacterial community had a most pronounced influence on ARGs (p < 0.05), and metabolites exhibited an important mediation effect on bacterial community (p < 0.05), thereby impacting ARGs. The metabolome analysis evidenced that significant correlations were found between defensive root exudates and most ARGs abundance (p < 0.05), like, luteolin-7-glucoside was negatively correlated with tetA(58). These findings provide deeper insights into the dynamics of soil ARGs under long-term fertilization, and identify critical factors that influence ARGs colonization in soils, providing support for controlling the spread of ARGs in agriculture soils.